Workplace sexual harassment: a qualitative study of the self-labelling process among employees in Denmark - Nielsen, Maj Britt Dahl; Skov, Sofie Smedegaard; Grundtvig, Gry; Folker, Anna Paldam; Rugulies, Reiner; Tybjerg Aldrich, Per; Clausen, Thomas; Madsen, Ida E. H. (International journal of qualitative studies on health and well-being, 2024)
To explore how employees understand work-related sexual harassment and label their experience. This study is based on 13 semi-structured in-depth interviews with employees exposed to workplace sexual harassment. We analysed the data using a thematic approach drawing on frameworks of sensemaking in organizations. We identified four major themes. The first two themes, and , outline the interviewees' definitions of the two terms "sexual harassment" and "unwanted sexual harassment" and reveal the challenges of labelling sexually harassing behaviours at work. The last two themes; and , explain the sensemaking process, i.e., how the interviewees come to understand and label their experience. The analysis showed that the interviewees related sexual harassment with physical, coercive, and intentional behaviours, whereas unwanted sexual attention was seen as less severe and less intentional. The interviewees often doubted how to label their experience, and making sense of one´s experience could take years. Self-labelling is inherently a social process, and the validation and rejection of others play an important role. Finally, the #MeToo movement constituted a turning point for several interviewees' understandings of events.